(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article examines the influence of international factors on the process of political modernization of Kyrgyzstan. The author explores the historical background, the main stages and modern features of the country’s political modernization, as well as analyzes the role of international relations, economic and cultural ties in this process. Special attention is paid to the analysis of the influence of international organizations, in particular, the United Nations, on the implementation of democratic transformations and the formation of civil society in Kyrgyzstan. It is concluded that international cooperation is a key factor in the successful implementation of political modernization and sustainable development of the country on the way to democracy and economic prosperity.